1989
DOI: 10.1002/app.1989.070370813
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics for the tensile strength degradation of nylon and kevlar yarns

Abstract: SynopsisThe tensile strength degradation of nylon 66 and Kevlar 29 yarns was studied. at elevated temperatures and over a broad range of relative humidities. The degradation rates for nylon are initially slow but increase rapidly, suggesting the depletion of an inhibitor. Kevlar showed no evidence for similar inhibitor action. The effect of relative humidity on degradation can be very large, especially at values in the 9C-100% range and at elevated temperatures. Degradation is governed by thermal-oxidative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…Several authors have discussed the underlying process of degradation [ 2,3,8,111. Auerbach [ 1 ] proposed a second order process and also considered the additional influence of an inhibitor at the beginning of degradation. He deduced the following equations in an integrated form:…”
Section: Time Dependent Treatments Tensile Modulusmentioning
confidence: 99%
“…Several authors have discussed the underlying process of degradation [ 2,3,8,111. Auerbach [ 1 ] proposed a second order process and also considered the additional influence of an inhibitor at the beginning of degradation. He deduced the following equations in an integrated form:…”
Section: Time Dependent Treatments Tensile Modulusmentioning
confidence: 99%
“…Twaron and Technora fibers both contain amide functions that are sensitive to hydrolysis 4,5 ; although, Imuro and Yoshida 6 reported that the dilution of aramid-linkages by ether-linkages as in Technora fibers may contribute to provide the latter with better hydrolytic stability. The mechanism of PPTA hydrolysis has been identified and involves scission of the amide NAC linkage, yielding acid and amine functions 4,5 (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts were made to fit the Auerbach [18] and Springer [19] degradation models to this strength data; however, the amount of degradation seen here is so minimal, and the failure distributions are so broad that a meaningful fit could not be obtained. Furthermore, there is no clear trend in the Weibull shape parameters for the strength, strain or modulus for all three materials.…”
Section: Mechanical Properties Determinationmentioning
confidence: 96%
“…Molecular spectroscopy was used to characterize chemical changes in the three fibers after ageing to determine what, if any, chemical changes occurred in the polymer. Two likely reactions that could occur in response to the hydrolytic environment are opening of the benzimidazole ring [39] and chain scission [16,18,19] at an amide bond. Schematics for these two potential reactions are presented for the fibers in Fig.…”
Section: Chemical Changes Due To Ageingmentioning
confidence: 99%
See 1 more Smart Citation